The military topography of Syria's south: Fickle external support for moderates. Resurgent Islamic State in birthplace of the revolt - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2016)
The Russian air attacks on Aleppo have diverted attention from Moscow's intervention intended to secure Bashar al-Assad's position in Damascus. Extending beyond northern Syria, Moscow's direct military involvement has instilled fear in the countries backing the non-Jihadist rebel units in the south. Known as the Southern Front, they are based in the area stretching from south of the capital to the Jordanian border and close to the Israeli border. Hardline Islamist rebels, as well as so-called Islamic State (IS), are poised to gain as moderates are undermined. A rethink on ways to empower the Southern Front and once more put pressure on Assad is overdue if the region and its civil structures are to escape capture by the regime and further penetration by the Jihadists is to be prevented - scenarios that could create a new wave of refugees towards Jordan. Due to the south's strategic importance, Israel has emerged as a veto player in the neighborhood, helping to curb Russian bombing as Moscow acts with different interests in the south and the north. (SWP Comments)
Keywords: 320